L’ereignis, Le Mot-Directeur De La PensÃ©e De Heidegger - Roy-Ema, Pascal DieudonnÃ© (European Scientific Journal, ESJ, 2017)
For over sixty years (from 1910 to 1973), Martin Heidegger carried out a work of thought which led him to create a large quantity of neologisms. It also led him to create a new use of idioms in the German language. This was regarded as a renewed vocabulary. His study bears new meanings and expresses the philosopher’s work of thought and the new concepts he proposes. Among them is the Ereignis that this text proposes to question the content. The Ereignis is what makes time and being belongs to each other. It is the relationship of all the relations engendered by this co-membership. This is made possible by the difference installed at the heart of the same. Heidegger himself admitted that the Ereignis was the keyword of his whole thought since the early 1930s. It is the word-director of his thought.